CONSERVATION STATUS OF AMORPHOPHALLUS DISCOPHORUS BACKER & ALDERW. (ARACEAE) IN JAVA, INDONESIA - Yuzammi Yuzammi (Research Center for Biology, 2014)
Amorphophallus discophorus Backer & Alderw. is one of the Javan endemic aroid species. This species is locally endemic to the slopes of Mount Wilis in Kediri Regency (East Java) at elevations between 600-1300 m. Poorly known species like A. discophorus could easily become extinct if not distinguished from other species, such as A. muelleri, that are used for commercial purposes. The conversion of natural forests for agriculture over the last decade has resulted in a loss of suitable habitat for this species. Several field trips undertaken to locate natural populations of this species have proved unsuccessful. Based on these field exercises, A. discophorus is regarded as presumed extinct in the wild.